NINGKATAN HASIL BELAJAR VOLUME BANGUN RUANG DENGAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING DI KELAS V SDN 10 BANDAR BUAT PADANG - Mardiah, Aina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research is backgrounded by learning volume of cube and block result has not gained KKM. The purpose of this search was to increase  the result of learning volume of cube and block using Contextual Teaching and Learning (CTL)  for class V students. This research was done in SDN 10 Bandar Buat Kota Padang. This type of research is Class Action Research (CAR). The approach is used a qualitative and quantitative approach. The subjects of the research are teacher and class V students as much as 28 people. The results of research to point out the CTL can improve the result of learning volume of cube and block for class V students.   Kata Kunci: hasil belajar volume bangun ruang; CTL